Note on certain subclass of close-to-convex functions of order α - Shigeyoshi Owa; M. K. Aouf; M. A. Nasr (International Journal of Mathematics and Mathematical Sciences)
The object of the present paper is to show a result for functions belonging to the class R(α) which is the subclass of close-to-convex functions in the unit disk U.